Local Government Strategies for the Preservation of Traditional Woven Sarongs as Cultural Heritage - Asfian; Muhammad Jamal; Muhammad Hairul Saleh (JGov: Journal of Governmentality, 2025)
This study explores the efforts of the Samarinda Seberang District Government in preserving Samarinda woven sarongs as a form of cultural heritage, addressing the gap in previous studies that mainly emphasized community participation. The urgency of this research lies in understanding how local government involvement contributes to sustaining cultural identity amidst modernization and globalization pressures. Theoretically, this study is grounded in cultural preservation and local governance frameworks, which view protection, development, and utilization as interrelated dimensions of heritage management. Using a qualitative descriptive method, data were collected through interviews, documentation, and literature review, and analyzed using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings reveal that the district government’s role in cultural preservation is relatively effective through protection, by legal and environmental safeguarding; development, through innovation and diversification of woven sarong products; and utilization, by promoting them as creative economic assets and integrating them into tourism and education. This study highlights that while these efforts are significant in reinforcing regional identity and empowering local artisans economically, they remain constrained by limited resources and inter-agency coordination. The results underscore the need for sustainable collaboration between government, community, and private sectors. In broader terms, this research contributes to the discourse on local governance and cultural sustainability, emphasizing that preserving cultural heritage is not only an act of identity protection but also a strategic pathway toward inclusive and sustainable regional development.